L-Carnitine Supplementation: A Potential Treatment for Cancer Cachexia - Kwong, Aaron; Khan, Obaidullah; Fleming, Katrina; Moshiri, Sina; Hashmi, Muhammad (The Meducator, 2014)
Cachexia is a paraneoplastic syndrome that exhibits rampant muscle wasting, unintentional weight loss, fatigue, weakness, and overall loss of appetite, none of which can be abated by an increase in caloric intake. Metabolic derailment by cachexia is so severe in cancer patients that it can shorten lifetime expectancy and lead to death before the course of treatment is finished. Etiology may involve proinflammatory cytokines, but the abnormal loss of muscle, protein, and fat suggests an underlying metabolic dysfunction that contributes to cachexia. Previous research has shown reduction of L-carnitine in cachectic patients and chemotherapy-induced damage to the L-carnitine transport system that may further exacerbate symptoms. As such, a possible avenue of treatment for cachexia-induced fat loss may involve L-carnitine supplementation to restore metabolic homeostasis through various mechanisms such as lowering levels of proinflammatory cytokines and restoring L-carnitine palmitoyltransferase activity. While the precise mechanism of L-carnitine=mediated amelioration has not been determined, research findings support the notion of L-carnitine as an alleviator of several cachectic symptoms that have previously been unmanageable in a clinical setting.